Longshore sorting on a beach under wave action - Celikoglu, Y; Yüksel, Y; Kabdasli, MS (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
Sorting of sediment on a beach under wave action takes several forms. Stratified layers of finer and coarser sediment, which depend on wave climate, grain size and beach slope are formed. This complex problem can be simplified by defining the cross-shore and longshore sorting according to the angle between the breaking wave and the coast. In the present study.. longshore distribution of sediment as well as corresponding beach profiles was measured in a wave basin. Three-dimensional hydraulic model experiments were performed with regular waves. Eighteen sets of experiments performed in longshore sorting mechanism using two different sand beds. The sorting of the bed material and the formation of armour coats along the beach were defined by grain size distributions and dimensionless parameters for sandy beaches. The rate of sediment transport with grain size sorting was measured in a wave basin. A method introduced sorting process was presented in this study. The sediment rate based on sorting mechanism was also discussed with known methods. It has been found that the nonuniformity of the grain size and hence sorting of the beaches play a very important role in the sand transport due to wave motion in a similar way to the case of steady flow in alluvial channels. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: longshore transport; coastal morphology; sorting; coastal sediment transport; Engineering; Oceanography